Butyronitrile emulsion as well as preparation method and application thereof
By adjusting the weight ratio of sulfur to accelerator and using zinc salt accelerators, the problem of rapid vulcanization and cross-linking of nitrile latex under low temperature and short-term conditions has been solved, and efficient production of nitrile latex products has been achieved while maintaining good mechanics. and appearance performance.
Patent Information
- Application Number
- CN202411634516.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art is difficult to achieve rapid vulcanization crosslinking of nitrile latex under low temperature short-term conditions, and the increase in the amount of a single component at low temperature will lead to frost spraying and the physical and mechanical properties of the material will be reduced.
By adjusting the weight ratio of sulfur to accelerator, the proportion of sulfur actually participating in the reaction is increased, and a zinc salt accelerator is used in combination to reduce the activation energy and promote the vulcanization reaction. At the same time, adjust the component ratio and processing conditions of the nitrile emulsion to ensure that the vulcanization reaction is completed in a short time.
The rapid vulcanization cross -linking of Dingjin lacta under low temperature and short -term conditions, maintaining good mechanical properties and appearance, shortening the product cycle, improving production efficiency, and reducing energy consumption.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of daily chemical rubber, and in particular relates to a nitrile emulsion and a preparation method and application thereof. Background Art
[0002] Most of the nitrile latex dipping molding uses a sulfur vulcanization system. On the one hand, sulfur is cheap and easy to disperse in latex; on the other hand, the system has a long processing window and can be stored for a long time at room temperature. Sulfur vulcanization molding can be achieved by heating.
[0003] Since the processing conditions of sulfur vulcanizers require high temperatures, sulfur reaches the melting point to form more activated sulfur sites, which can increase the cross-linking density of the vulcanized rubber and improve the vulcanization efficiency. Alternatively, the vulcanization time can be increased to increase the cross-linking opportunities of the activated sulfur sites of the vulcanized rubber, thereby increasing the cross-linking density of sulfur. However, facing the current mass production requirements, this method is difficult to implement, the upper limit is low, and the goal of high speed, high yield and low carbon cannot be achieved.
[0004] Article 1009-797X(2021)02-0006-04, "Research on Improving the Cross-linking Density of Nitrile Gloves", discloses a research method for improving the cross-linking density of nitrile gloves. The method adopts increasing the temperature, increasing the time and increasing the amount of accelerator. However, this method does not solve the problem of achieving rapid cross-linking of nitrile latex under low temperature and short-time conditions. After the amount of a single component is increased to saturation, frosting will occur and the physical and mechanical properties of the material will be reduced.
[0005] Therefore, the prior art lacks a method for preparing a nitrile emulsion and a rubber product that can achieve rapid vulcanization and cross-linking of rubber under low temperature conditions and has good mechanical properties and appearance. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical defects and provide a nitrile emulsion which can realize rapid vulcanization and cross-linking of rubber under low temperature and short time conditions and has good mechanical properties and appearance.
[0007] Another object of the present invention is to provide a preparation process of the nitrile emulsion and rubber product.
[0008] Another object of the present invention is to provide an application of the above-mentioned nitrile emulsion.
[0009] The present invention is achieved through the following technical solutions: A nitrile emulsion, comprising the following components by weight: 90-110 parts of nitrile latex; Emulsifier 0.1-1.2 parts; 0.5-2.5 parts of acid-base regulator; Zinc oxide 1.0-3.0 parts; 3.4-5.4 parts of vulcanization package; The weight proportion of the nitrile latex is the weight proportion of the dry rubber; The vulcanization package is composed of sulfur and an accelerator, and the weight ratio of sulfur to the accelerator is (1.5-2.5):1; The accelerator is selected from zinc salt accelerators.
[0010] Preferably, the nitrile latex is selected from carboxyl nitrile latex.
[0011] Further preferably, the nitrile latex is selected from butadiene-acrylonitrile and -methacrylic acid terpolymer latex.
[0012] The invention can increase the amount of sulfur actually participating in the reaction by limiting the weight ratio range of sulfur to accelerator, thereby increasing the cross-linking reaction rate.
[0013] The proportion of activated sulfur in a single sulfur molecule is relatively low, at 7%-10%. Adding an accelerator in a specific ratio can reduce the activation energy and act as an activator. The accelerator has 5-6 sites participating in the reaction. When there are enough sites, the amount of activated sulfur is increased, and the proportion of sulfur participating in the reaction is increased, which will positively promote the vulcanization reaction.
[0014] Furthermore, nitrile rubber is a rubber latex made from butadiene, acrylonitrile and methacrylic acid by emulsion copolymerization. It contains hydrophilic and strongly polar carboxyl groups on the main chain of the molecule, which makes the latex easy to cross-link and can also react with divalent metal oxides or their salts to form ionic cross-linking bonds.
[0015] The reaction rate can also be controlled by adjusting the number of vulcanization packages.
[0016] The traditional formula uses a high sulfur content and a low accelerator content, and requires a long time of room temperature vulcanization during the preparation process. The carboxyl content in the latex is relatively excessive, and most of it does not participate in the reaction. The traditional formula has a long processing cycle and low production capacity. Compared with the traditional formula, the nitrile emulsion provided by the present invention makes full use of the carboxyl and accelerator in the latex, effectively improving the vulcanization reaction speed.
[0017] Zinc salt accelerators have low activation energy and only require 100°C for activation. At the same time, zinc salt accelerators have a short scorch time, which is conducive to rapid molding of impregnation, faster dehydration condensation, a denser structure inside the film, faster heating evaporation efficiency, and faster thermal vulcanization speed.
[0018] Preferably, the nitrile emulsion comprises the following components by weight: 95-105 parts of nitrile latex; Emulsifier 0.3-1.0 part; 1.0-2.0 parts of acid-base regulator; Zinc oxide 1.5-2.5 parts; 3.4-4.5 parts of vulcanization package.
[0019] Preferably, the mass content of acrylonitrile in the nitrile latex is 23%-27%.
[0020] Preferably, the content of carboxyl groups in the nitrile latex accounts for 1-7wt% of the weight of the dry rubber in the nitrile latex.
[0021] Preferably, the emulsifier is selected from at least one of sodium dodecylbenzene sulfonate, ammonium dodecyl sulfate, sodium dodecyl sulfate or sodium secondary alkyl sulfonate.
[0022] Preferably, the acid-base regulator is selected from potassium hydroxide.
[0023] Preferably, the sulfur is selected from elemental sulfur.
[0024] Preferably, the zinc salt accelerator is selected from at least two of zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, zinc ethylphenyldithiocarbamate or zinc diisobutyldithiocarbamate.
[0025] More preferably, the zinc salt accelerator is selected from a mixture of zinc diethyldithiocarbamate and zinc diisobutyldithiocarbamate; the mass ratio of zinc diethyldithiocarbamate to zinc diisobutyldithiocarbamate is (1-2): (1-2).
[0026] There are two promoting groups and two activating groups in the dithiocarbamate accelerator, and there are highly active and easily broken strong polar sulfur-zinc bonds. In the vulcanization reaction, there are 3-4 times more activation sites than ordinary accelerators. At the same time, adding a matching amount of sulfur can greatly increase the vulcanization speed; the easily broken strong polar sulfur-zinc bonds reduce the activation energy, open the bonds quickly, and have a short scorch time. Monosulfide bonds and polysulfide bonds can be quickly formed, thereby forming a dense cross-linked rubber network.
[0027] The present invention also provides a method for preparing a rubber product, comprising the following steps: S1: Weigh each component by weight, stir for no less than 20 hours, and then add deionized water to prepare the nitrile latex of the required concentration for standby use; S2: preparing a demoulding liquid, wherein the demoulding liquid comprises, by weight, 10-30 parts of a coagulant, 1-3 parts of a release agent, and 67-89 parts of deionized water, and each component is weighed by weight and stirred to mix evenly; the coagulant is selected from at least one of calcium nitrate, magnesium nitrate, and calcium chloride, and the release agent is selected from at least one of calcium stearate, sodium stearate, and zinc stearate; S3: cleaning the mold with acid and alkali and drying it; immersing the dried mold in the demoulding liquid of S2, taking it out and rotating it to dry it; S4: the mold after the release liquid is dried is immersed in the diluted nitrile latex in S1, and is taken out and rotated to dry; the mold is immersed in the diluted nitrile latex in S1 again, and is taken out and rotated to dry for the second time; S5: The dried mold is filtered with clean water, hot vulcanized, demoulded and packaged.
[0028] Preferably, in step S1, the acid-base regulator is added in the form of a solution having a concentration of 0.5-4.0 wt %.
[0029] Preferably, in step S1, zinc oxide is added in the form of an emulsified zinc oxide emulsion.
[0030] Preferably, in step S1, the vulcanization package is added in the form of a mixed solution of sulfur and an accelerator, and the preparation method of the mixed solution is to mix and grind the sulfur and the accelerator to reach a stable suspended mixed solution state.
[0031] Preferably, the solid content of the nitrile emulsion diluted with deionized water in step S1 is 10-40wt%.
[0032] Preferably, the optimal processing window of the nitrile latex described in S1 is 20 hours to 40 hours.
[0033] The accelerator, zinc oxide and sulfur first generate polysulfide compounds of the accelerator, which then react with rubber molecules to form rubber thiol. The rubber thiol then undergoes cross-linking reactions with rubber molecules or itself, and finally undergoes rearrangement, shortening, main chain modification, etc. to form vulcanized rubber.
[0034] Preferably, the acid-base cleaning temperature in S3 is 40-70° C., the acid ion concentration is 1-6wt%, and the alkali ion concentration is 3-8wt%.
[0035] Preferably, the temperature of the demoulding liquid in S3 is 50-70°C, and the drying temperature is 60-100°C.
[0036] Preferably, the nitrile latex temperature in S4 is 25-35°C, and the drying temperature is 60-100°C.
[0037] Preferably, the vulcanization temperature in S5 is 80-100° C., and the vulcanization time is 10 to 15 minutes.
[0038] The present invention also provides a rubber product, which is prepared by using the above-mentioned nitrile emulsion.
[0039] Preferably, the rubber product is a glove.
[0040] Compared with the prior art, the present invention has the following beneficial effects: The traditional hot vulcanization time of nitrile latex dipping molding is 25-40 minutes. The nitrile emulsion and preparation method provided by the present invention can achieve rapid vulcanization and cross-linking of nitrile latex by hot vulcanization at 100°C for 15 minutes, and has good mechanical and appearance properties. The cycle of preparing nitrile products from nitrile emulsion is greatly shortened, the production efficiency is increased by 1 times, and the energy consumption is reduced by 30%, which can reduce a lot of costs for the production process. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0042] The raw materials used in the present invention come from: Nitrile latex 1: LG NL105, the carboxyl content accounts for 1-2wt% of the dry rubber weight, Ningbo LG Yongxing Chemical Co., Ltd.
[0043] Emulsifier: LAS-30, sodium dodecylbenzene sulfonate, Jiangsu Qingting Detergent Co., Ltd.
[0044] Acid-base regulator: KOH, Huarong Chemical (Chengdu) Co., Ltd., added in the form of a diluted solution with a concentration of 2 wt%.
[0045] Zinc oxide: ZnO, Guangzhou Li Xin Trading Co., Ltd.
[0046] Accelerator 1: Zinc diethyldithiocarbamate ZDEC Guangzhou Li Xin Trading Co., Ltd.
[0047] Accelerator 2: Zinc diisobutyl dithiocarbamate ZDIBC Guangzhou Li Xin Trading Co., Ltd.
[0048] Accelerator 3: Tetramethylthiuram disulfide TMTD Guangzhou Li Xin Trading Co., Ltd.
[0049] Sulfur: S Guangzhou Li Xin Trading Co., Ltd.
[0050] Calcium nitrate: Calcium nitrate Jiaocheng Sanxi Chemical Co., Ltd.
[0051] Calcium stearate: MAXCO B101 Guangzhou Murphy Environmental Protection Technology Co., Ltd.
[0052] Various test methods: Tensile strength: According to the ASTM D5034-2017 standard method, the sample is uniformly cut into dumbbells with a length of 115 mm and a width of 6 mm. The standard test temperature is 23 ± 2 ° C, and the relative humidity is maintained at 50 ± 5%. The experiment is carried out on a motor-driven machine with a uniform speed of 500 ± 50 mm / min, and the distance is at least 750 mm.
[0053] Elongation at break: According to ASTM D5034-2017 standard method. 13 samples were cut with a standard cutter and the results were averaged.
[0054] Vulcanization speed: According to the GB / T 25268-2010 Rubber Vulcanizer User Guide, the rubber compound is made into a dry rubber block, and 6g-8g of sample is put into the rubber vulcanizer. The test conditions are 100℃, 60min. T90 represents the vulcanization time when the rubber compound reaches the best performance state, which is also the positive vulcanization time in the process. T90=[ML+(MH-ML)x90%] corresponds to the time. The positive vulcanization time is also the time slightly before the tensile strength reaches the highest point. Because rubber products will continue to vulcanize during storage, they will not be completely vulcanized in actual production. It is enough to achieve product performance. On the one hand, it can save costs, and on the other hand, it can extend the product life. T70 is the vulcanization time when nitrile rubber products can achieve product performance in actual production. T70=[ML+(MH-ML)x70%].
[0055] Appearance test: Place at room temperature for 30 days, and observe with the naked eye under fluorescent light to see if there is frost.
[0056] The preparation methods of the embodiments and comparative examples of the present invention are as follows: S1: Weigh each component by weight, stir for 20 hours, and then add deionized water to dilute the nitrile emulsion to a solid content of 40wt%; S2: preparing a demoulding liquid, which comprises, by weight, 20 parts of a coagulant, 2 parts of a release agent, and 80 parts of deionized water, and weighing each component by weight and stirring and mixing them evenly; the coagulant is selected from calcium nitrate, and the release agent is selected from calcium stearate; S3: After the production line equipment is verified to be qualified, the mold is cleaned with acid and alkali and dried at 70℃, with an acid ion concentration of 5% and an alkali ion concentration of 5%. The mold is immersed in a 60℃ demoulding liquid and then taken out and dried at 80℃. S4: the mold is immersed in 30°C nitrile latex, taken out and dried at 80°C; the mold is immersed in nitrile latex again, and taken out and dried at 80°C for the second time; S5: The mold is filtered with clean water, hot-cured at 100℃ for 15 minutes, demoulded, and packaged.
[0057] Table 1 Weight parts of each component of nitrile emulsion of Examples 1-9 and test results thereof
[0058] In Example 2-5, the weight ratio of accelerator to sulfur was 2, but the amount of vulcanization package added was increased.
[0059] In Examples 6-8, the weight ratio of accelerator to sulfur was gradually increased when the addition amount of the vulcanization package was 4.2.
[0060] It can be seen from Examples 1-9 that the rubber products prepared by the nitrile emulsion provided by the present invention have a breaking force ≥6N, a tensile strength ≥32MPa, and an elongation at break ≥500%.
[0061] Table 2 Weight parts of each component of nitrile emulsion of Comparative Examples 1-6 and test results
[0062] It can be seen from Comparative Examples 1 and 2 that a too low weight ratio of the accelerator to sulfur will lead to an increase in the vulcanization time, and a too low or too high weight ratio of the accelerator to sulfur will lead to frosting on the appearance.
[0063] It can be seen from Comparative Examples 3 and 4 that too low or too high an amount of the vulcanization package added will increase the vulcanization time, and too high an amount of the vulcanization package added will cause frosting on the appearance.
[0064] It can be seen from Comparative Examples 5 and 6 that the use of non-zinc salt accelerators significantly increases the vulcanization time.
Claims
1. A nitrile emulsion, characterized in that By weight, it includes the following components: 90-110 parts of nitrile latex; Emulsifier 0.1-1.2 parts; 0.5-2.5 parts of acid-base regulator; Zinc oxide 1.0-3.0 parts; 3.4-5.4 parts of vulcanization package; The weight proportion of the nitrile latex is the weight proportion of the dry rubber; The vulcanization package is composed of sulfur and an accelerator, and the weight ratio of sulfur to the accelerator is (1.5-2.5):1; The accelerator is selected from zinc salt accelerators.
2. The nitrile emulsion according to claim 1, characterized in that The content of carboxyl groups in the nitrile latex accounts for 1-7wt% of the dry rubber weight in the nitrile latex.
3. The nitrile emulsion according to claim 1, characterized in that The emulsifier is selected from at least one of sodium dodecylbenzene sulfonate, ammonium dodecyl sulfate, sodium dodecyl sulfate or sodium secondary alkyl sulfonate.
4. The nitrile emulsion according to claim 1, characterized in that The acid-base regulator is selected from potassium hydroxide; the sulfur is selected from elemental sulfur.
5. The nitrile emulsion according to claim 1, characterized in that The zinc salt accelerator is selected from at least two of zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, zinc ethylphenyldithiocarbamate or zinc diisobutyldithiocarbamate; preferably, the zinc salt accelerator is selected from a mixture of zinc diethyldithiocarbamate and zinc diisobutyldithiocarbamate.
6. A method for preparing a rubber product, characterized in that: The following steps are involved: S1: Weigh the components of the nitrile emulsion according to any one of claims 1 to 5 by weight, stir them thoroughly and dilute them for later use; S2: prepare demoulding liquid for standby use; S3: cleaning and drying the mold; The dried mold is immersed in the demoulding liquid of S2, taken out and dried again; S4: Dipping the mold after the release liquid is dried into the diluted nitrile emulsion in S1, taking it out and drying it; dipping the mold into the diluted nitrile emulsion in S1 again, taking it out and drying it for the second time; S5: The mold after drying is subjected to leaching, hot vulcanization, demoulding and packaging to obtain the rubber product.
7. The method for preparing a rubber product according to claim 6, characterized in that: In step S1, the acid-base regulator is added in the form of a solution with a concentration of 0.5-4.0 wt%.
8. The method for preparing a rubber product according to claim 6, characterized in that: In step S1, zinc oxide is added in the form of an emulsified zinc oxide emulsion.
9. The method for preparing a rubber product according to claim 6, characterized in that: In step S1, the vulcanization package is added in the form of a mixed liquid of sulfur and an accelerator, and the preparation method of the mixed liquid is to mix and grind the sulfur and the accelerator to reach a stable suspended mixed liquid state.
10. A rubber product, characterized in that: It is prepared using the nitrile emulsion described in any one of claims 1 to 5; the rubber product is preferably a glove.
Citation Information
Patent Citations
Anti-aging butyronitrile material and application thereof
CN112778589A
Carboxylic butyronitrile emulsion as well as preparation method and application thereof
CN114672082A
Butyronitrile gloves and preparation method thereof
CN114766766A
Low-temperature vulcanization bag group as well as preparation method and application thereof
CN114854057A
Latex composition for dip molding and dip-molded article including the same
GB202102139D0